2017
DOI: 10.1097/md.0000000000009224
|View full text |Cite
|
Sign up to set email alerts
|

Poorer prognosis in patients with advanced gastric squamous cell carcinoma compared with adenocarcinoma of the stomach

Abstract: Rationale:Primary squamous cell carcinoma (SCC) of the stomach is a rare disease. The pathogenesis and prognosis of advanced SCC remains to be elucidated. The aim of the current study was to investigate the prognosis of recurrent or metastatic SCC of the stomach.Patient concerns:A retrospective study examined the clinical characteristics and survival outcomes of 14 patients diagnosed with recurrent or metastatic SCC of the stomach, including 7 patients followed up in the hospital and 7 patients selected from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Unfortunately, because of its advanced stage upon diagnosis, the majority of the patients are not surgical candidate; various palliative chemo regimens including fluoropyrimidine-based, platin-based and taxane-based combined chemotherapy have been reported. With these chemotherapies, primary gastric SCC has an overall survival ranging from 2 to 22 months (median 7 months) in the previous reports, usually longer in patients who had surgery with a progression-free survival of 10 months from the date of surgery to recurrence or metastasis 13. In two case reports with concurrent chemoradiotherapy, the overall survival was actually increased to 27 months17 and 60 months 18.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Unfortunately, because of its advanced stage upon diagnosis, the majority of the patients are not surgical candidate; various palliative chemo regimens including fluoropyrimidine-based, platin-based and taxane-based combined chemotherapy have been reported. With these chemotherapies, primary gastric SCC has an overall survival ranging from 2 to 22 months (median 7 months) in the previous reports, usually longer in patients who had surgery with a progression-free survival of 10 months from the date of surgery to recurrence or metastasis 13. In two case reports with concurrent chemoradiotherapy, the overall survival was actually increased to 27 months17 and 60 months 18.…”
Section: Discussionmentioning
confidence: 96%
“…Because of its rarity, understandings of primary gastric SCC are mainly based on case reports and case series studies 13. Gastric SCC predominantly affects male patients with an age of around 60,13 14 and abdominal pain and weight loss are the two most common symptoms. The most common location of the tumour is lesser curvature, followed by greater curvature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other alternatives used are platin and taxane-based regimens. These include docetaxel + oxaliplatin/cisplatin + fluorouracil (DOF), fluorouracil + oxaliplatin + calcium folinate (FOLFOX), capecitabine + oxaliplatin (XELOX), docetaxel + capecitabine, cisplatin + fluorouracil/campitabine/S-1, docetaxel + cisplatin/oxaliplatin (TP), gemcitabine + fluorouracil (GF) and pirabucin + fluorouracil [ 10 ]. It is important to mention that some reports have found neoadjuvant chemotherapy for PGSCC to be effective [ 4 ]; however, there is no definitive role according to the available data [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…A new retrospective study published by Meng et al showed a poorer prognosis in patients with advanced gastric SCC, compared with adenocarcinoma of the stomach, with a median survival of seven months [ 10 ]. This is due to the advanced stage at the time of diagnosis [ 8 - 9 ].…”
Section: Discussionmentioning
confidence: 99%